ZEOLITES CHEMICAL FERTILIZATION OF CACAO CCN-51 ASSOCIATED - Sánchez Mora, Fernando David (2014)
The effect of two commercial zeolites of the clinoptilolite type was evaluated: Roca Magica® (RM) and Zeolite C® (ZC), included in the chemical fertilization on the production and profitability of cocoa “CCN-51” of sexual origin, associated with four timber species, caoba de montaña (Colubrina arborescens (Mill.) Sarg), fernánsanchez (Triplaris cumingiana F.), guayacán blanco (Cybistax donell-smithii Rose) and laurel prieto (Cordia macrantha Chadat). For fertilization two different levels (25 and 30%) of two types of zeolite (RM and ZC) were used. Fertilization experiments were divided into three parts, applying urea, MgSO4, K2O and P2O5. A split plot design was used with four timber species, five subtreatments (types and levels of zeolite) and four replications. Cocoa phenology (sprouting, flowering, fruiting) as well as cherelles wilt, healthy pods number and cocoa production in kg ha-1 was measured. Cocoa plants associated with fernánsanchez issued the highest number of outbreaks in the rainy season, probably due to the lower air coverage of the species. The highest fructification of cacao was achieved in the rainy season with fernánsanchez and guayacán associations, applying 30% of ZC. The highest number of healthy pods, and cocoa production was obtained with fernánsanchez association in the dry season, while the highist profitability was found with fernánsanchez and 25% of RM.